Pengembangan Dan Pengujian Dinamometer Berbasiskan Strain Gauge Dengan Batang Regang Tipe Four Square Stalk Untuk Pengukuran Gaya Potong Mesin Bubut - Donara, Geovanny; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Dinamometer is an instrumentation that function for measure the cutting force on the lathe machine. The dynamometer principle use a strain gauge that is to utilize the strain that occurs on the strain bar as a reader in Voltage units then converted into force units in Newton. The strain on the strain bar is read by strain gauge,, then amplified using amplifier (signal amplifier) so it can be read and displayed on the LCD (Liquid Crystal Display) and storing data measurement results on the computer (PC) using Data Logger. Research that has been done before there are still some weaknesses which need to be developed in this research. To get the measurement result of the dynamometer, development begins with changes in the dimension of the strain bar and changing the type of material on the part of the dynamometer which experienced strain and modifications are made to the electrical circuit of the dynamometer. Then do the process of finding correlation between Depth of Cut with Cutting force. The purpose of finding correlations between these two variables is to get correlation factor which will be incorporated into the arduino program. Methods in finding correlation factor used is by giving a disruption of loading, the loading is given through a two-way force that is tangential direction loading and axial direction loading.Keywords : Cutting Force, Strain Bar, Stress, Wheatstone Bridge, Correlation Factor.